Influence Of Green Marketing, Product Quality, and Promotion On Consumer Satisfaction at Skincare Stores In BELOPA - Sulfitra Sulfitra; Suhardi M. Anwar; Junaidi Junaidi (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to examine the effects of green marketing, product quality, and promotion on consumer satisfaction at a skincare store in Belopa, Luwu Regency, South Sulawesi. Methodology: A quantitative research approach was used through a survey method by distributing questionnaires to consumers with a sample size of (n=30), and the data were analyzed using statistical techniques. Results: The results show that all variables have a significant effect on consumer satisfaction, both simultaneously and partially, with product quality as the most dominant factor. Findings: Consumers place high value on product effectiveness and environmental responsibility, which contribute to their satisfaction. Novelty & Originality: The novelty of this study lies in integrating green marketing with traditional marketing variables in the context of a local skincare business, particularly in Belopa, a region rarely examined in prior research. Conclusions: In conclusion, improving product quality, implementing effective green marketing strategies, and optimizing promotional activities can enhance consumer satisfaction and loyalty. Type of Paper: This paper is an empirical research paper.